2019
DOI: 10.1161/strokeaha.119.025692
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Central Poststroke Pain

Abstract: Background and Purpose— Central poststroke pain (CPSP) is a disabling condition in stroke patients, and evidence suggests that altered corticospinal and motor intracortical excitability occurs in neuropathic pain. The objective of this study was to investigate changes in motor cortex excitability and sensorimotor interaction and their correlates with clinical manifestations and alterations in somatosensory systems in CPSP patients. Methods— Fourteen pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 38 publications
4
54
0
Order By: Relevance
“…Retaining physical capacity and independence was identified as an important aspect of QOL [36]. This is in line with Dysvik et al [10], who identified that each of the subscales of the SF-36 were lower where pain was present; the greatest effect was on physical role, referring to limitations in daily activities. Lack of independence can cause depression which can lower motivation to be physically active [58].…”
Section: Physical Functionsupporting
confidence: 77%
See 2 more Smart Citations
“…Retaining physical capacity and independence was identified as an important aspect of QOL [36]. This is in line with Dysvik et al [10], who identified that each of the subscales of the SF-36 were lower where pain was present; the greatest effect was on physical role, referring to limitations in daily activities. Lack of independence can cause depression which can lower motivation to be physically active [58].…”
Section: Physical Functionsupporting
confidence: 77%
“…The overall experience of pain appeared to have a consistent and negative impact on QOL. Several studies support this finding [8][9][10]. Pain was reported to have no impact on QOL [28] when the BPI was used, an outcome measure that has not been validated for use in a stroke population.…”
Section: Painmentioning
confidence: 95%
See 1 more Smart Citation
“…First, for overcoming the relatively small sample size, we undertook the analyses by comparing three groups: CPSP, stroke control, and normal control. In addition, we enrolled the larger numbers of sample size compared to previous studies [ 16 , 20 , 21 ]. Thus, we drew out the alterations of white matter for CPSP.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was an observational investigation of CPSP, so the exact sample size was not calculated beforehand. However, the sample sizes of previous studies varied from 2 to 14 [ 16 , 20 , 21 ]; thus, it was determined that the sample size for this study would be more than 14 subjects. Moreover, to increase the accuracy of our results, we decided to include a stroke control group 1.5 times the size of the CPSP group and a normal control group twice the size of the CPSP group.…”
Section: Methodsmentioning
confidence: 99%